2011
DOI: 10.1161/strokeaha.111.631200
|View full text |Cite
|
Sign up to set email alerts
|

Late-Phase Contrast-Enhanced Ultrasound Reflects Biological Features of Instability in Human Carotid Atherosclerosis

Abstract: Background and Purpose-Development of translational functional imaging modalities for atherosclerosis risk stratification is sought for stroke prediction. Our group has developed late-phase contrast-enhanced ultrasound (LP-CEUS) to quantify microbubble contrast retention within carotid atherosclerosis and shown it to separate asymptomatic plaques from those responsible for recent cerebrovascular events. We hypothesized that microbubbles are retained in areas of plaque inflammation, aiming to examine whether LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 7 publications
0
21
0
5
Order By: Relevance
“…19,115 A number of inflammatory markers including matrix metalloproteinase-9 (MMP-9) are highly expressed in enhancing plaques. 50,91 Studies comparing plaque enhancement in asymptomatic and symptomatic plaques have demonstrated that plaque enhancement is markedly increased in patients with symptomatic plaque and is associated with a higher rate of cardiovascular events in general. 102,122,130 Retention of microbubbles on the plaque surface on delayed images has been shown to correlate with plaque disruption and inflammation as macrophages are known to phagocytose this contrast agent.…”
Section: Ceusmentioning
confidence: 99%
“…19,115 A number of inflammatory markers including matrix metalloproteinase-9 (MMP-9) are highly expressed in enhancing plaques. 50,91 Studies comparing plaque enhancement in asymptomatic and symptomatic plaques have demonstrated that plaque enhancement is markedly increased in patients with symptomatic plaque and is associated with a higher rate of cardiovascular events in general. 102,122,130 Retention of microbubbles on the plaque surface on delayed images has been shown to correlate with plaque disruption and inflammation as macrophages are known to phagocytose this contrast agent.…”
Section: Ceusmentioning
confidence: 99%
“…1 Recently, contrast-enhanced ultrasound (CEUS) has been introduced for the evaluation of carotid atherosclerosis and plaque vulnerability by identifying the presence of intraplaque neovascularization. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The present review provides a brief overview of the commonly used ultrasound techniques for the evaluation of carotid atherosclerosis and subsequently focuses on the role of CEUS for the assessment of carotid atherosclerosis and plaque instability. The promising results of the initial CEUS studies in humans are discussed.…”
mentioning
confidence: 99%
“…2,6,16,17 Thus, it is speculated that correlations may also exist between spatial and temporal parameters. Here, correlations between the two types of parameters are reported for the first time.…”
Section: Discussionmentioning
confidence: 99%